ASSA14-03-30 Long-term Efficacy of PCI vs CABG for Patients with Multiple Coronary Chronic Total Occlusions. (1st December 2014) - Jian, Z; Ya-Ling, H; Quanmin, J; Xiaozeng, W; Ying-Yan, M; Geng, W; Bin, W
Abstract : Backgroud: Data on the efficacy of percutaneous coronary intervention (PCI) for treatment of multiple coronary chronic total occlusion (CTO) lesions are scanty. The optimal revascularisation strategy for multiple coronary CTO disease in the era of drug-eluting stents (DES) has become more controversial between coronary artery bypass grafting (CABG) and PCI. The aim of the present study is to compare the long-term outcomes of DES implantation for multiple coronary CTO lesions compared with CABG. Methods: We analysed 261 patients who underwent coronary angiography for at least two de novo CTO lesions in our centre from November 2000 to November 2006. Among them, 118 patients (45.2%) received DES implantation after recanalisation for CTO lesions and 143 patients (54.8%) received CABG. Major adverse cardiac and cerebrovascular events (MACCE: death, acute myocardial infarction, stroke and repeat revascularisation) and hospitalisation costs were compared. Long-term survival rates were estimated with the Kaplan-Meier method. Results: Patients in the CABG group were likely to have hyperlipidemia, diabetes mellitus, multivessel disease and higher euroSCORE. The mean follow-up was 4.2 ± 0.7 years in the CABG group and 4.3 ± 0.5 years in the DES group. Total hospitalisation costs were lower (p = 0.017) in the CABG group (median: 107 thousand Yuan) than in the DES group (median: 156 thousand Yuan). Rates of MACCE at 12 months were higher in the PCI group (16.9% vs 11.2% for CABG; P = 0.179), but not statistically significant, in large part because of an increased rate of repeat revascularisation (15.3% vs 7.0%, p = 0.016). The overall survival rate (CABG: 73.4% and DES: 76.2% at 5 years, p = 0.599) and the TVR-free survival rate did not differ between the groups. Conclusions: This study demonstrates the long-term (up to 5 years) efficacy and safety of DES for treatment of multiple coronary CTO lesions. The long-term survival rate of PCI with DES was comparable to that of CABG for the treatment of multiple coronary CTO. PCI with DES was more costly than CABG. PCI using DES might be an alternative to CABG in selected patients with multiple coronary CTO disease.